Wawasan Al-Qur’an Tentang Misaq (Sebuah Kajian Tafsir Maudu’i) - Muammar Muchtar; H. Mubarak Bakri; Masri Saad (AL-AQWAM: Jurnal Studi Al-Quran dan Tafsir, 2022)
It is important to independently propose a study of the protocol (misaq). There’s a lot to explore about this topic, depending on what perspective and approach is used. At the same time, the views of tafsir (Qur’anic) and hadiths are still rarely touched upon. Independent study from the perspective of the Qur’an is an urgent attempt to obtain a complete view of this object. From the tracing of the misaq scriptures and the exposition of related research, it can be seen that the firm covenant of man and god (misaqan ghalizan) in the first three aspects, the covenant between man and God in the context of the implementation of religious teachings, is confirmed in the womb of man while he is still in the womb, second, the covenant between God and the prophet to publish his treatises, and the third is the covenant of harmony and peace between husband and wife. All these treaties are again firmly bound and will be accounted for in the future.